Effect of theileriosis on the reproductive function of Boran/Friesian cross heifers - Rumberia, Rufus Mburea (The University of Edinburgh, 1992)
This thesis describes studies that were undertaken to evaluate the effect of T. parva infection on the reproductive function of Boran/Friesian cross heifers. The study was conducted in four separate experiments. In Experiments 1 and 2, the animals were monitored for cyclical status post-infection. In Experiments 3 and 4, the infected animals were divided into two groups: one group was monitored for cyclical status and the other for both cyclical and pregnancy status after exposure to a bull. The reproductive function was assessed by routine monitoring of oestrus behaviour, palpation of the genital reproductive tract per rectum and determination of serum progesterone (P4) concentrations. Further, in view of observed acyclicity in the early work, attempts were made to assess the pituitary response to gonadotrophin releasing hormone (GnRH) in a group of animals (Ch. 5) in an attempt to explain partly the mechanisms involved in the impairment. Animals were monitored for the progression of disease by clinical and parasitological responses. Further, subject to death or sacrifice, a macroscopic and histological examination of target and various other organs and tissues was undertaken in an effort to establish the part played by observable pathological changes in the development of impaired reproductive function. In Experiment 1, ten heifers were infected with 1:20 T. parva stabilate while four others remained as uninfected controls. Two of the infected animals died, one each on days 17 and 29. Clinical reactions in the recovered animals ranged from mild to moderate. P4 profiles and ovarian structures revealed that three of eight recovered animals had luteal dysfunction post-infection although two of the three showed clinical oestrus during this particular period. The other five recovered animals cycled regularly. The results from clinical and pathological studies did not indicate any direct adverse effect of infection on reproductive function. All the four controls cycled throughout the study period. In Experiment 2, ten animals were infected with an undiluted stabilate while four others acted as uninfected controls. Eight of ten infected animals died of severe disease. Of the eight fatal cases, six were cyclic pre- and post-infection based on P4 profiles, ovarian structures and/or behavioural data. P4 profiles and ovarian structures revealed that the other two animals were acyclic before and after infection although clinical oestrus was detected in both pre-infection. Both of the recovered animals underwent extended periods of acyclicity post-infection. There was no evidence linking the acyclicity to the active parasitosis or pathological changes observed in the reproductive organs. All control animals cycled throughout the study period. In Experiment 3, 14 heifers were infected with undiluted stabilate and treated at the height of clinical reaction. One of eight animals subjected to serial kill, was acyclic before and after infection based on P4 profile and ovarian changes although it was seen in heat pre-infection. Of the remaining seven, one animal became acyclic while all the other six revealed clinical oestrus or/and cyclical ovarian changes after infection. Two of six animals exposed to a bull became pregnant while the others were cycling regularly at seven months post-infection. All controls cycled throughout the study period. In Experiment 4, eight animals were immunized by infection and treatment method while four others acted as uninfected controls. Three of four animals monitored for cyclicity cycled regularly post-immunization. The other had a persistent corpus luteum which regressed spontaneously after an extended luteal period of 42 days and cycled regularly subsequently. One of four animals exposed to a bull became pregnant while the others cycled regularly to week 20 post-immunization. All the controls cycled throughout the study period. The evidence from the four experiments indicated that T. parva did not directly affect reproductive function. Pathological lesions were observed in the reproductive organs but these were mild and did not affect normal reproductive physiological activity. It is postulated that the impaired reproductive function was due to an indirect effect linked to loss in condition following infection.
The effect of theileriosis on the reproductive function of Boran/Friesian cross heifers